Analyzing the Similarity between Abagusii and Judean Conception of God as Reflected in the Book of Ruth - Charles K. Moywaywa; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
The belief that God, or the Supreme Being, is the source of all that exists is common among a wide range of African communities that still retain a good measure of their traditional religio-cultural heritage. The Abagusii of Western Kenya is one of the communities that has been exposed to and actually embraced the western culture. This notwithstanding, the Abagusii are still proud of their traditional customs and still maintain a good measure of these practices, either in their original form or with modifications. In this paper we examine the influence of belief in God on the day-to-day activities of the Abagusii and assess the similarity of their religiosity with that of the Judeans as reflected in the book of Ruth. The purpose of this work is to contribute to the on-going debate on inculturation by projecting a trajectory that appreciates the authenticity of all cultures. In comparing the similarity between Abagusii and Judean conception of and interaction with the divine, this paper covers the following key areas: the nature and function of God, human limitations, the relationship between God and humans, the notion of divine intervention, and the influence of religious consciousness on the daily life of the community and its members. The author is cognizant that the Book of Ruth may not provide a comprehensive picture of the Judean concept of God. But it provides a basis for a comparative study on the way community members utilized their religious awareness and identity to govern their daily lives.